2023
DOI: 10.1055/s-0043-1776298
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Distraction Osteogenesis

Heather R. Burns,
Daniel S. Wang,
Amjed Abu-Ghname
et al.

Abstract: Distraction osteogenesis (DO) of the craniofacial skeleton has become an effective technique for the treatment of both nonsyndromic and syndromic conditions. The advent of craniofacial DO has allowed for earlier intervention in pediatric patients with less complication risk and morbidity compared to traditional techniques. In this review, we will discuss current application and technique for craniofacial DO by anatomical region and explore future applications in craniofacial surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 93 publications
(220 reference statements)
0
1
0
Order By: Relevance
“…In addition, we observed that vertical and sagittal mandibular dysplasia contributed to airway narrowing and chin retraction. With the help of preoperative virtual design technology, we were able to execute osteotomy precisely with surgical guides and accurately design the number and position of the distraction hardware [ 27 ]. Possible issues during the distraction period can also be simulated and predicted in advance [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed that vertical and sagittal mandibular dysplasia contributed to airway narrowing and chin retraction. With the help of preoperative virtual design technology, we were able to execute osteotomy precisely with surgical guides and accurately design the number and position of the distraction hardware [ 27 ]. Possible issues during the distraction period can also be simulated and predicted in advance [ 28 ].…”
Section: Discussionmentioning
confidence: 99%